Follow up survey of monthly Gonokendra (Bangladesh Rural Advancement Committee, Research and Evaluation Division, 1978)
Report of a 1978 survey evaluating the distribution system and audience of the monthly Gaṇakendra, published by the Bangladesh Rural Advancement Committee.